2012
DOI: 10.1183/09031936.00022912
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and tolerability of linezolid containing regimens in treating MDR-TB and XDR-TB: systematic review and meta-analysis

Abstract: Linezolid is used off-label to treat multidrug-resistant tuberculosis (MDR-TB) in absence of systematic evidence. We performed a systematic review and meta-analysis on efficacy, safety and tolerability of linezolid-containing regimes based on individual data analysis.12 studies (11 countries from three continents) reporting complete information on safety, tolerability, efficacy of linezolid-containing regimes in treating MDR-TB cases were identified based on Preferred Reporting Items for Systematic Reviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
280
1
12

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(303 citation statements)
references
References 46 publications
10
280
1
12
Order By: Relevance
“…Recent studies have shown that regimens containing Lzd for the treatment of XDR-TB result in more rapid culture conversion compared with regimens without Lzd [18,19]. The main drawback of Lzd is the high risk of adverse events, although lowering the dose from 600 mg to 300 mg might be beneficial [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that regimens containing Lzd for the treatment of XDR-TB result in more rapid culture conversion compared with regimens without Lzd [18,19]. The main drawback of Lzd is the high risk of adverse events, although lowering the dose from 600 mg to 300 mg might be beneficial [19].…”
Section: Discussionmentioning
confidence: 99%
“…• Ideally use at least four drugs, in addition to pyrazinamide, to which the strain has proven or probable susceptibility (drugs previously taken for ≥1 month are generally avoided) 238 • Use a backbone of a later-generation fluoroquinolone (eg, moxifloxacin or levofloxacin; group A drug), plus a second-line injectable drug (amikacin or kanamycin, or capreomycin; group B drugs; used for ≥4 months after culture conversion and for a minimum of 6 months) 238 • Add any first-line drug and additional group C drugs (eg, cycloserine or terizidone, ethionamide or prothionamide, clofazimine, or linezolid if appropriate) to which the isolate is susceptible • The WHO recommended treatment duration is 20 months; however, this recommendation is based on very low-quality evidence) 238 • Bedaquiline or delamanid (group D2) can be added to the regimen if toxicity or resistance precludes formulation of a regimen containing ≥4 drugs that are likely to be effective, particularly if a group A or B drug cannot be used (both prolong QT interval, and thus require monitoring) 270,271 • Oxazolidinones (linezolid) can be used (group C drug), particularly in fluoroquinolone-resistant MDR or XDR tuberculosis, but monitoring for toxicity (neuropathy and bone marrow suppression) is required 272,273,274 • Given the specific and conditional nature of the recommendation (poor-quality evidence), the decision to use the newer WHO-recommended 9-12-month short course versus the ~20-month regimen in selected patients will be dependent on several factors, including previous treatment, local resistance profiles, patient acceptance, and the requirement for proven or highly likely fluoroquinolone and aminoglycoside isolate susceptibility, and absence of probable or proven resistance to any of the components of the regimen (except isoniazid) 68 • Whatever the duration of the regimen used, psychosocial and financial support are crucial elements to maintain adherence • Patients should be monitored for adverse drug reactions, which are common 275 • A single drug should not be added to a failing regimen • The patient's HIV status should be established and antiretroviral therapy initiated in all HIV-infected patients…”
Section: Mdr Tuberculosismentioning
confidence: 99%
“…343 Linezolid has been used off-label in patients with MDR tuberculosis with promising efficacy in observational studies. 272 The addition of linezolid to a failing regimen in patients with XDR tuberculosis resulted in culture conversion in 87% of patients by 6 months, and resistance emerged in 4 of 38 patients. 344 In another trial in which patients with XDR tuberculosis were randomised to receive linezolid or placebo, added to an individually optimised treatment regimen, culture conversion at 24 months was significantly higher for patients receiving linezolid (79% vs 38%).…”
Section: Oxazolidinonesmentioning
confidence: 99%
“…However, it is lacking of dosage instruction during treatment. No significant differences were detected in the subgroup efficacy analysis (daily linezolid dosage ≤ 600 mg versus >600 mg) [22], even a lower linezolid dosage of 300 mg daily apparently achieved good efficacy [23]. Moreover, the optimum duration of linezolid use to treat MDR-TB is still unknown.…”
Section: Off-label Use Of Anti-tb Drugsmentioning
confidence: 99%
“…A number of case reports and respective studies have been performed to evaluate the efficacy of the regimens containing linezolid in the treatment of MDR and XDR TB [19][20][21]. The systematic review suggested that linezolid use significantly increased the probability of a favourable outcome [22]. However, it is lacking of dosage instruction during treatment.…”
Section: Off-label Use Of Anti-tb Drugsmentioning
confidence: 99%